The anxieties of mobility : migration and tourism in the Indonesian borderlands - Lindquist, Johan (Southeast Asia--politics, meaning, memory., 2009)
Since the late 1960s the Indonesian island of Batam has been transformed from a sleepy fishing village to a booming frontier town, where foreign investment, mostly from neighboring Singapore, converges with inexpensive land and labor. Export processing zones such as Batam are both celebrated and vilified in contemporary debates on economic globalization. The Anxieties of Mobility moves beyond these dichotomies to explore the experiences of migrants and tourists who pass through Batam. Johan Lindquist's extensive fieldwork allows him to portray globalization in terms of relationships that bind individuals together over long distances rather than as a series of impersonal economic transactions. He offers a unique ethnographic perspective, drawing together the worlds of factory workers and prostitutes, migrants and tourists, and creating a compelling account of everyday life in a borderland characterized by dramatic capitalist expansion. The book uses three Indonesian concepts (merantau, malu, liar) to shed light on the mobility of migrants and tourists on Batam. The first refers to a person's relationship with home while in the process of migration. The second signifies the shame or embarrassment felt when one is between accepted roles and emotional states. The third, liar, literally means "wild" and is used to identify those who are out of place, notably squatters, couples in premarital cohabitation, and prostitutes without pimps. These sometimes overlapping concepts allow the book to move across geographical and metaphorical boundaries and between various economies. The Anxieties of Mobility is an ideal text for courses dealing with gender, globalization, and anthropology.